Interaction of Industry Development with its Encoding in Rceat: Experience of Veterinary Medication Production - G. M. Samoilov (Вестник Российского экономического университета имени Г. В. Плеханова)
In public space prospects of development of industries in Russian economy that put out new goods and services are often connected with giving these industries relative codes in the Russian Classifier of Economic Activity Types (RCEAT). The article analyses the case of giving RCEAT code to producers of medication for veterinary use: arguments of industry representatives were studied, open statistic information was summarized and assessed and certain elements of the system of state regulation were discussed that use the classifier of economic activity types. It was shown that availability of RCEAT code does not impact directly on results of industry development, on the contrary industry success can speed up the decision about giving it a special code in order to improve efficiency of state governance. On the basis of research conclusions proposals aimed at specification of methodology for collecting industry statistic information were put forward. At the same time representatives of other industries were recommended to supplement arguments for giving new RCEAT codes with estimation of economic effects and detailed description of concrete procedures of state governance, within the frames of which classifier upgrading can foster the development of a certain industry.